Effect of tufting on the mechanical behaviour of carbon fabric/epoxy composites - Dell'Anno, Giuseppe (Cranfield University, 2007)
This work draws some early baselines on the in-plane/out-of-plane properties balance in a 5HS woven carbon fabric/epoxy composite reinforced by tufting and resin injected by resin transfer moulding technique. Details of the manufacturing processes involved in the preparation of such through-the-thickness reinforced composites are presented together with analysis of the mesostructure of tufted specimens. Preforms were reinforced locally with a commercial glass or carbon fibre thread. The tufts were inserted in square arrangement with a KSL tufting tool interfaced to a 6 axis computer controlled robot arm from Kawasaki. The presence of tufts improved significantly the delamination resistance, assessed by testing double cantilever beam coupons in mode I loading configuration. In-plane tension and compression after im¬pact (CAI) tests revealed that the reinforcement resulted in a considerable increase in the post-impact residual strength value, with an accompanying drop down in static tensile modulus and strength of less than 10%. In addition to the standard coupons for the determination of the quasi-static mechanical properties, some cured miniature specimens containing a limited number of tufts were also prepared. These were tested in both uniaxial pull-out and in a mode II configuration in order to measure the bridg¬ing actions of the tufts and to determine the micromechanical failure mechanisms. The obtained crack bridging laws were used for calibrating a simple analytical model of the mechanical behaviour of a single tuft within the composite. The tufting technology was applied to an innovative concept that aims to adopt the tufting threads as a carrier for resin modifiers. For this purpose a single-filament and a multi-filament thermoplastic prototype threads were used. These threads are not intended to modify the composite fibre architecture but are expected to dissolve into and react with the host matrix upon cure. The outcome of mode I delamination and CAI tests conducted on woven preforms reinforced with such `soluble' threads are presented and discussed.